Synthesis, characterization and molecular docking studies of novel S-substituted phenacyl-1,3,4-thiadiazole-thiol derivatives as antimicrobial agents - Kerur, Shashidhar; Alagawadi, Kallanagouda; Zhu, Hailiang; Manvi, Fakkirappa (European Journal of Chemistry, 2012)
In the present study, synthesis and antimicrobial activity of 2,5-disubstituted 1,3,4-thiadiazole derivatives 5a-f are described. The structures of the newly synthesized compounds were confirmed by FT-IR, 1H NMR, 13C NMR, mass and elemental analysis. All compounds were screened for antitubercular and antimicrobial activity. Molecular modeling studies were performed to dock compounds into the ecKAS III binding site, which suggested probable inhibition mechanism. The results revealed that most of the compounds showed high to moderate biological activity against tested microorganisms.